Osteological Study on the Proximal row of Carpal Bones in Indian Elephant (Elephas maximus indicus) - P. J. KAPADNIS; S. K. GUPTA; S. K. KARMORE (Indian Journal of Veterinary Anatomy, 2025)
The present study was conducted on the proximal row of carpal bones of fore limb in Indian elephant (Elephas maximus indicus). In the present study the short carpal bones were eight in number and were arranged in two rows. From medial to lateral side the proximal row consisted of radial, intermediate, ulnar and accessory carpals. The radial carpal was nearly small, truncated pyramid shaped bone. Proximally this bone was narrower than distally. It articulated proximally with the radius and distally with 1st and 2nd carpal bones of distal row. The ulnar carpal bone was the largest bone of the proximal row and roughly triangular in shape. The intermediate carpal bone was wedge shaped. The accessory carpal bone was falciform in shape and had only one articular surface which articulated with the posterior (palmar) surface of the ulnar carpal.